Uji toksisitas zat warna azo turunan odianisidin terhadap saccharomyces cerrevisae sebagai model uji ekotoksikologis = Toxicity test of O-dianisidine Azo Dyes to Saccharomyces cerrevisiae as A Model Ecotoxikological Test - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
O-dianisidine azo dyes are used in coloring processes of Indonesian batik industries. The toxicity of azo compuond is defined by its degradation, i.e. amine aromatic compound, nevertheless the toxicity of its parent compound is still unknown. There are posibilities to describe ecotoxicological interactions of xenobiotic using QSAR-model. The aim of this study is having more information of cause-effect relationship of xenobiotic o-dianisidine azo dyes toward Saccharomyces cerrevisae, as an eucaryotic model. The experiment begin with lipophilicity parameter determination (log k octanol/water, and log k paraffine/ water) followed by ecotoxicological parameter (EC 50). The determination of lipophilicity was carried out in two ways